THE INFLUENCE OF ANNICK COJEAN’S THOUGHTS IN THE BOOK GADDAFI’S HAREM ON FORMER LIBYAN PRESIDENT MUAMMAR GADDAFI - Hadiyanto, Ahmad Fajri; Amanda, Arizka (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
This study examines Annick Cojean’s perspectives in her work Gaddafi’s Harem regarding the figure of Muammar Gaddafi in Libya. The research employs historical methods as its primary approach. The findings indicate that Cojean portrays Gaddafi through orientalist and feminist perspectives, while also highlighting the biases of Western media, which are perceived as hypocritical. As an orientalist, Cojean is considered to have certain aims and agendas behind her work, namely, constructing a negative image of the Islamic world. She is perceived as a 'puppet' of greater powers, with 'puppet masters' who hold broader agendas toward the Middle East in order to impose a World Order, thereby subjugating the Islamic world. The book Gaddafi’s Harem is divided into two main parts. The first part emphasizes the story of Soraya, the central character who, according to Cojean’s narrative, experienced sexual abuse by Gaddafi. The second part focuses on the role of Gaddafi’s supporters and close circle in maintaining his hegemony for 42 years. Keywords: annick cojean, gaddafi harem, libya, thought